Demographic and Clinical Features of Uveitis in Tertiary Centers in Turkey - (:unkn) unknown (TAYLOR & FRANCIS INC, 2008)
Purpose: To analyze the referral patterns and clinical features of uveitis in tertiary eye care centers in Turkey. Methods: Uveitis services of eight university clinics collected data on uveitis patients who presented during 2004. Data were collected on a form including a questionnaire on socio-demographic and clinical features which were documented at presentation. Results: A total of 761 patients (1187 eyes) with a mean age of 35.5 years were included in the study. Male to female ratio was 1.04:1. The majority of patients (89.6%) were from an urban population, 53% were referrals and 43% had had uveitis for more than one year. The most common type of uveitis was anterior uveitis (52.5%) followed by panuveitis (28.1%), posterior uveitis (12.7%) and intermediate uveitis (6.7%). In 56.8% of patients an etiological classification was established. The most common etiology was Behcet's disease (32.1%), followed by Fuchs' heterochromic iridocyclitis (5.1%) and ocular toxoplasmosis (4.7%). Among 48 pediatric patients uveitis associated with juvenile idiopathic arthritis and ocular toxoplasmosis both having equal frequencies (12.5%) were the most common diagnosis. These were followed by Behcet's disease with juvenile-onset (10.4%). At the time of presentation, 6.25% of the patients were legally blind (having visual acuity less than 0.1 in the better seeing eye). Conclusion: Compared to the uveitis series reported from other countries, Behcet uveitis was the leading cause of uveitis in this series. Uveitis associated with juvenile idiopathic arthritis and ocular toxoplasmosis were the most common cause of uveitis in childhood. On the other hand, entities like acquired immunodeficiency syndrome-related uveitis, presumed ocular histoplasmosis and Birdshot retinochoroidopathy were rare.
Keywords: Epidemiology; uveitis; tertiary centers; etiology; ENDOGENOUS UVEITIS; PEDIATRIC UVEITIS; PATTERNS; DISEASE; POPULATION